Upaya Peningkatan Kesadaran Akan Perilaku Hidup Bersih dan Pencegahan Demam Berdarah Dengue (DBD) di RW 033 Desa Sumber Jaya Bekasi - Bagus Wicaksono; Muhammad Sulthon Auliyaa; Afgan Sandy Putra; Devy Juliani; Hilal Ghufron; Muhammad Luthfi Nugeraha; Jarot Usman Sahadat; Shafwan Nadhif; Muhammad Razaqa Dhi'fan Dwi Putra; Nur Aeni; M. Reza Syahputra (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
The Real Work Lecture Program carried out by Group 4 aims to increase public awareness in Sumber Jaya Village, especially in RW 033 regarding clean living behavior and prevention of Dengue Hemorrhagic Fever (DHF). The KKN program that willbe carried out consists of the main activities in the form of carrying out community service work, socializing about a healthyenvironment and dengue fever as well as giving lavender plants, naming plants around the RW 033 post with a QR Code,socializing children with the media of painting piggy banks, and making a bank. inorganic waste. Through these programs, it is hoped that it can increase people's awareness of healthy living in a clean environment, broaden people's knowledge aboutdengue fever in a deeper way, use technological media in the form of SCcan QR Code as an educational development for localresidents regarding plants and their uses, increase awareness of life. cleanliness for children from an early age, and fostering awareness of the importance of waste management to support efforts to improve healthy living in preventing dengue fever. From the activities that have been carried out, it turns out that the KKN carried out by Group 5 in Sumber Jaya village has succeeded in having a positive impact on the community and the environment.